Testicular lymphoma of 63 patients: a Chinese retrospective, real-world study - Qiao, Honghan; Zhang, Sijun; Duan, Yukai; Hua, Renjie; Zong, Feiyang; Zhang, Mingzhi; Zhang, Xudong (Frontiers in Oncology, 2025)
ObjectiveTo suggest the difference between primary and secondary testicular lymphoma, and to manifest the clinical characteristics, treatment modalities and prognostic factors of primary testicular lymphoma.MethodThis study included all lymphoma patients with testicular involvement treated at our institution between October 2012 and May 2024. We retrospectively collected data on their clinical characteristics, treatment approaches, and outcomes for further analysis.ResultA total of 50 primary testicular lymphoma (PTL) patients and 13 secondary testicular lymphoma (STL) patients were enrolled, with diffuse large B-cell lymphoma (DLBCL) being the most common subtype. After a median follow-up of 36.0 months (range: 1.1–117.5), the median progression-free survival (PFS) was 105.9 months for PTL patients and 16.8 months for STL patients. The median overall survival (OS) was 106 months for PTL and 23.8 months for STL. Among the 46 primary DLBCL (PT-DLBCL) cases, half received central nervous system (CNS) prophylaxis, and 7 patients (15.2%) experienced CNS relapse. Patients who received maintenance therapy after orchiectomy and first-line treatment exhibited prolonged PFS. Radiotherapy was associated with improved PFS, while the double-expressor phenotype was linked to poorer OS.ConclusionPTL suggested distinct histopathological features, clinical responses, and survival outcomes compared to STL. A combined treatment strategy involving orchiectomy followed by chemotherapy, consolidation therapy, and radiotherapy is recommended for PT-DLBCL. As intrathecal methotrexate did not significantly reduce CNS recurrence, alternative prophylactic strategies should be explored for high-risk patients.